2012
DOI: 10.1016/j.neurobiolaging.2011.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Increased regional cerebral glucose uptake in an APP/PS1 model of Alzheimer's disease

Abstract: Alzheimer’s disease (AD), the most common age-related neurodegenerative disorder, is characterized by the invariant cerebral accumulation of β-amyloid peptide. This event occurs early in the disease process. In humans, [18F]-Fluoro-2-deoxy-D-Glucose-Positron Emission Tomography ([18F]-FDG-PET) is largely used to follow-up in vivo cerebral glucose utilisation (CGU) and brain metabolism modifications associated to the AD pathology. Here, [18F]-FDG-PET was used to study age-related changes of CGU under resting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
95
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 51 publications
(63 reference statements)
8
95
1
2
Order By: Relevance
“…Furthermore, normalized 18 F-FDG uptake, a small-animal PET marker for glucose metabolism, was elevated in PS2APP mice, especially in the young group and to a lesser extent still at 16 mo of age, compared with findings in WT groups. This seems in line with previous reports of elevated relative glucose metabolism in amyloid models, such as APP/PS1 (27) and 5xFAD (28) mice, in which glial activation was discussed as a probable factor. However, this interpretation seems at odds with 18 F-FDG findings in human AD and in prodromal patients with amnesic mild cognitive impairment (29).…”
Section: Neuroinflammation In Tg Mouse Model Of Adsupporting
confidence: 93%
“…Furthermore, normalized 18 F-FDG uptake, a small-animal PET marker for glucose metabolism, was elevated in PS2APP mice, especially in the young group and to a lesser extent still at 16 mo of age, compared with findings in WT groups. This seems in line with previous reports of elevated relative glucose metabolism in amyloid models, such as APP/PS1 (27) and 5xFAD (28) mice, in which glial activation was discussed as a probable factor. However, this interpretation seems at odds with 18 F-FDG findings in human AD and in prodromal patients with amnesic mild cognitive impairment (29).…”
Section: Neuroinflammation In Tg Mouse Model Of Adsupporting
confidence: 93%
“…In 3-, 6-, and 12-month-old tg-AD mice, it was found that there was an age-dependent increase in glucose uptake in the cortex, hippocampus, and striatum, areas associated with high plaque accumulation (54). However, this study did not discern what proportion of glucose was processed by aerobic glycolysis versus mitochondrial respiration.…”
Section: Discussioncontrasting
confidence: 66%
“…The 7-month-old Tg2576 mice show an increased cerebral glucose uptake 27 and the APP/PS1 mouse model revealed increased glucose uptake only close to plaques but not in amyloid-free cerebral tissues 28 and increased basal metabolic rate of cells surrounding amyloid plaques. 29 The 5XFAD mouse model of AD also showed an increased brain glucose uptake.…”
Section: Effect Of Lipoic Acidmentioning
confidence: 99%